ПРОБЛЕМА ЦИФРОВОГО РОЗРИВУ КРІЗЬ ПРИЗМУ КВАЛІФІКАЦІЙНОЇ НЕВІДПОВІДНОСТІ РОБОЧОЇ СИЛИ. - О. І., Бондаренко (Hileya: Scientific Bulletin / Gileya, 2024)
The article examines the problem of the digital divide through the prism of the qualification mismatch of the workforce. The purpose of the study is to explore the problem of the digital skills gap in the labor market of developed economies and the solving the problem through the spread of digital skills. The analysis showed that the digital divide was initially considered from the standpoint of technological determinism, but with the introduction of digital technologies, the problem of providing the economy with the necessary labor resources with digital skills arose. Consequently, the emphasis in understanding the digital divide has shifted to the social sphere, exacerbating the problem of personnel qualification mismatch. The EU countries conduct politics of the digital divide reduction. The ongoing digital transformation of the economy and society requires that all Europeans develop digital skills, as outlined in the Digital Decade strategy. In particular, the workforce needs advanced training to use new digital technologies in the workplace. The development and implementation of advanced digital technologies in every sector of economy also requires a large pool of highly qualified IT specialists. Thus, creating conditions for improving digital skills in the workplace becomes necessary for companies. The EU government is aware that those countries will be competitive, whose labor resources will meet the new technological conditions, therefore the adopted decisions have a systemic political nature.